Cocreative Transformational Learning as a Way to Break Out of Script. (2nd January 2020) - Robinson, Paul
Abstract: This article describes a process of generating and facilitating a cocreated learning space that supports transformational change for the participants through a process of transformational learning. It tells the story of the formulation of the process and identifies and explores some of the main models and theories involved in its generation and operation. This story has a beginning but not an ending because the exploration and analysis is ongoing. It provides a methodology for generating and experiencing the process and the transformational outcomes. The author raises questions for readers to reflect on in relation to their own practice.